MODEL KEPEMIMPINAN PENDIDIKAN KH HASYIM ASY'ARI: ANALISIS HISTORIS TERHADAP KONSEP ADAB AL-'ALIM WA AL-MUTA'ALLIM - Mukhtari, Al (NIHAYAH: Journal of Islamic Studies, 2025)
This article explores the historical construction and contemporary relevance of the concept Adab al-‘Alim wa al-Muta‘allim in the thought of KH Hasyim Asy’ari, positioning it as a model of Islamic educational leadership grounded in the local wisdom of the pesantren tradition. In the pesantren context, adab is not merely a set of ethical norms but serves as an epistemological foundation for the educator-student relationship, synthesizing elements of Islamic jurisprudence (fiqh), Sufism (tasawuf), and Javanese cultural values. This study employs a qualitative approach through intellectual history and case study methods. Data were collected through textual analysis of the Adab al-‘Alim wa al-Muta‘allim manuscript, historical documentation of Tebuireng Pesantren (1900–1947), interviews with pesantren leaders, and participatory observation at three pesantren that continue to implement the concept. The findings reveal that KH Hasyim Asy’ari developed the adab framework as a response to colonial moral degradation and as a pillar for educational leadership rooted in spirituality and scholarship. This concept integrates scholarly authority with charismatic values in the kiai–santri relationship, remaining relevant amid the crisis of ethics in modern education systems. The study concludes that KH Hasyim Asy’ari’s concept of adab offers strong potential for integration into national education systems, particularly in fostering character and ethical leadership based on spiritual and local values. Further cross-regional research is recommended to develop an applicable leadership model across diverse pesantren contexts.